Upaya Meningkatkan Hasil Belajar Dan Kemampuan Gerak Dasar Permainan Rounders Melalui Strategi Pembelajaran Berpasangan Siswa Kelas V SD Negeri 112 Pacciro Kabupaten Bone - haderiah haderiah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
The problem in this study is that most students lack basic motion in the rounders game. The effort taken is to implement a pairing learning strategy. The purpose of this study was to improve the basic mobility of rounders through pairing strategies in the fifth grade of SD Pacciro Elementary School, Ajangale District, Bone District 2017/2018 Academic Year. The object of the research is an increase in ball catching abilities in Rounders ball games. Research time for 6 months. Data collection techniques using observation, test and documentation methods. The data that has been obtained is then presented using descriptive statistics. From the results of classroom action research carried out that the application of the pairing learning strategy had a positive impact on improving the scholarship throwing ability of the fifth grade of SD Negeri 112 Pacciro Ajangale Subdistrict Bone District 2017/2018 Academic Year, this can be proven to increase student learning outcomes characterized by increased yields and completeness of student learning in each cycle. So it can be concluded that the application of paired learning strategies is proven to be able to improve the basic motion ability of ball catching at rounders game CLASS V SD Negeri 112 Pacciro Ajangale District Bone District 2017/2018 Academic Year.